Pemanfaatan Lahan Kosong untuk Budidaya Penanaman Vanili dalam Rangka Meningkatkan Perekonomian Desa Sinabun, Kecamatan Sawan, Kabupaten Buleleng, Propinsi Bali - Thom Deutmar Londo Doaly; I Ketut Wenten; Alexander Raphael; Chaidir Djohar (Abdimisi, 2021)
Community Service (PKM) is in collaboration with Sinabun Village, Sawan sub-district, Buleleng Regency, Bali Province, Indonesia. The villagers of Sinabun Village are mostly farmers, who have land that can be used to increase their income. Vanilli is currently a plant that has a high selling value that can be planted by utilizing vacant land owned by villagers. However, villagers are also faced with the ability to manage financial administration and taxation. So that the purpose of this activity is (1) hopefully that it can increase the income of villagers through planting or cultivating vanilla by utilizing vacant land, (2) to get an adequate understanding of village financial administration records or village accounting and (3) getting an adequate understanding of taxation in general. Community Service was carried out through counselling, discussion and direct question and answer in Sinabun Village on Saturday, May 29, 2021. The results of the activity which was attended by approximately 20 villagers that residents realized that vacant land could be utilized and the importance of financial and tax administration. This Community Service is expected to be useful for various parties including residents and the Sinabun Village community in particular, students, academics and the wider community in general.